Study of the Basic Parameters Characterized the (D-T) Hot Plasma Fusion Reaction In General Dense Plasma Focus Devices - Raad Hameed Majeed (Journal of Madenat Alelem University College, 2012)
Plasma focus devices can be considered (PFD) as a strong source for the elementary charge particles, neutrons, protons, and soft x-rays are the main reason for its importance in many experimental applications. The dependency of the basically hot plasma parameters such as reactivity, reaction rate, and energy of the emitted neutrons, upon the total cross section of D-T fusion reaction still up to now the essential factor governed the primary calculations, and accuracy, for both experimental and theoretical studies. Formulism describing the physical behavior of a given experiment still varies from others experiments and indeed, a theoretical modification for the empirical formulas plays a rule to achieve compatible results.